A Novel Pathogenic Variant in CARMIL2 (RLTPR) Causing CARMIL2 Deficiency and EBV-Associated Smooth Muscle Tumors - Yonkof, Jennifer R.; Gupta, Ajay; Rueda, Cesar M.; Mangray, Shamlal; Prince, Benjamin T.; Rangarajan, Hemalatha G.; Alshahrani, Mohammad; Varga, Elizabeth; Cripe, Timothy P.; Abraham, Roshini S. (Frontiers in Immunology, 2020)
CARMIL2 deficiency is a rare combined immunodeficiency (CID) characterized by defective CD28-mediated T cell co-stimulation, altered cytoskeletal dynamics, and susceptibility to Epstein Barr Virus smooth muscle tumors (EBV-SMTs). Case reports associated with EBV-SMTs are limited. We describe herein a novel homozygous CARMIL2 variant (c.1364_1393del) in two Saudi Arabian male siblings born to consanguineous parents who developed EBV-SMTs. CARMIL2 protein expression was significantly reduced in CD4+ T cells and CD8+ T cells. T cell proliferation on stimulation with soluble (s) anti-CD3 or (s) anti-CD3 plus anti-CD28 antibodies was close to absent in the proband, confirming altered CD28-mediated co-signaling. CD28 expression was substantially reduced in the proband's T cells, and was diminished to a lesser degree in the T cells of the younger sibling, who has a milder clinical phenotype. Defects in both T and B cell compartments were observed, including absent central memory CD8+ T cells, and decreased frequencies of total and class-switched memory B cells. FOXP3+ regulatory T cells (Treg) were also quantitatively decreased, and furthermore CD25 expression within the Treg subset was substantially reduced. These data confirm the pathogenicity of this novel loss-of-function (LOF) variant in CARMIL2 and expand the genotypic and phenotypic spectrum of CIDs associated with EBV-SMTs.